Externalities in Recruiting - Matthias Kräkel; Nora Szech; Frauke von Bieberstein (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
External recruiting at least weakly improves the quality of the pool of applicants, but the incentive implications are less clear. Using a contest model, this paper investigates the pure incentive effects of external recruiting. Our results show that if workers are heterogeneous, the opening of a firm's career system may lead to a homogenization of the pool of contestants and, thus, encourage the firm's high ability workers to exert more effort. If this positive effect outweighs the discouragement of low ability workers, the firm will benefit from external recruiting. If, however, the discouragement effect dominates the homogenization effect, the firm should disregard external recruiting. In addition, product market competition makes opening of the career system less attractive for a firm since it increases the incentives of its competitors' workers and hence strengthens the competitors.
urn:nbn:de:bvb:19-epub-17239-1
Keywords: C72; J2; J3; 330; contest; externalities; recruiting; wage policy